Comparative Study of Antimicrobial (Triclosan) Coated Versus Conventional Suture Material in Preventing Surgical Site Infections - V, Deepak; Murthy, J. Sathyanarayana; Arun Balaji MS; MS, A.P. Subburaaj; MS, J. Sridhar (Journal of Neonatal Surgery, 2025)
Background and Objectives: Surgical site infections (SSIs) remain a prevalent complication across various surgical procedures, leading to increased morbidity, prolonged hospital stays, and financial burdens on healthcare systems. This study aims to evaluate the efficacy of antimicrobial (triclosan) coated suture material compared to conventional sutures in reducing SSIs when used for subcutaneous closure. Methods: A prospective observational study was conducted over 18 months at Vinayaka Missions Kirupananda Variyar Medical College and Hospital, Salem. A total of 200 patients undergoing day-care surgical procedures were divided into two groups: Group A (n=100) received conventional 2-0 vicryl sutures, while Group B (n=100) received triclosan-coated 2-0 vicryl sutures for subcutaneous closure. Patients were followed up for two months to assess the incidence of SSIs. Data were analyzed using SPSS 23.0, employing statistical methods such as frequency counts, percentages, and the Chi-square test. Results: The age distribution was similar in both groups (Mean ± SD: 50.39 ± 17.32 years in Group A and 51.56 ± 15.85 years in Group B, p=0.61). Gender distribution was also comparable (p=0.67). Diagnoses included lipoma, hydrocele, sebaceous cyst, fibroadenoma, and dermoid cyst, with no significant difference between groups (p=0.97). The prevalence of Type II Diabetes Mellitus was significantly higher in the control group (p<0.0001). At the first follow-up, the normal healing rate was significantly higher in Group B (85% vs. 50% in Group A, p<0.0001). The need for additional treatments such as absorbent dressing and culture & sensitivity testing was lower in the triclosan-coated suture group (p=0.0006). By the second follow-up, 89% of patients in Group B had a healthy scar with complete wound healing, whereas 75% in Group A exhibited normal healing patterns (p=0.002). Conclusion: The use of antimicrobial (triclosan) coated sutures significantly reduces the incidence of SSIs, improves wound healing, and minimizes the need for additional interventions. Triclosan-coated sutures are a promising option for improving surgical outcomes, particularly in patients with high-risk factors for SSIs.